PRIORITIZING THE RENEWABLE ENERGY TECHNOLOGIES IN TANAKEKE ISLAND, SOUTH SULAWESI: AN AHP APPROACH - azizah fauziah misbahuddin; Afif Fahmi Misbahuddin (Jurusan Pendidikan Teknik Elektro, 2025)
The transition toward sustainable and decentralized energy systems has heightened the urgency for renewable energy adoption, particularly in off-grid and remote areas. In Indonesia, many island communities remain disconnected from the central electricity grid and face chronic energy access issues. One such case is the Tanakeke Archipelago, located in Takalar Regency, South Sulawesi, where residents experience limited and unreliable electricity supply despite ongoing government electrification programs. This study aims to identify the most suitable renewable energy technology for Tanakeke Island using the Analytic Hierarchy Process (AHP), involving six key criteria: local natural resource potential, technical feasibility, investment and operational costs, system reliability, social acceptance, and environmental impact. Four alternative technologies were evaluated: Solar Power Plant (PLTS), Wind Power Plant (PLTB), Wave Power Generator (PLTO), and Micro Hydro Power Plant (PLTMH). Expert input was gathered from academics and local community figures. The results indicate that Wind Power Plant (PLTB) ranks highest with a global priority score of 2.72, followed by Solar Power Plant (PLTS) with 1.78, Wave Power Generator (PLTO) with 1.09, and Micro Hydro Power Plant (PLTMH) with 0.41. Among the six criteria, Technical Feasibility held the highest weight (0.32), followed by Local Resource Potential (0.25) and Investment Cost (0.21). These findings highlight that technical and resource-based considerations are the most influential in determining the appropriate energy solution for Tanakeke Island. This study provides a structured and data-driven approach to aid local governments and stakeholders in planning sustainable and context-appropriate energy infrastructure in underserved island communities.